THE PRIORITY FOR IMPROVEMENT VEHICLE PARKING SERVICE AT EL TARI KUPANG AIRPORT USING QUALITY FUNCTION DEPLOYMENT (QFD). - Amy Wadu; Achmad Wicaksono (Universitas Islam Malang, 2020)
El Tari Kupang Airport is one of the airports in the Province of East Nusa Tenggara (NTT) with a growing rate of passenger movement increasing every year. In line with the increase in passenger movement growth, the use of vehicles to enter the airport area is increasing. This results in the need for handling parking facilities to provide proper security and comfort to airport visitors. The method used in this research is the Quality Function Deployment (QFD) method to determine the priority of parking service handling. Based on the results of QFD, the priority order for handling that must be immediately implemented is to provide training to parking officers so that they have the ability to manage traffic in the parking area.